Loose porous carbon box conductive agent carbon material, preparation method thereof and application of loose porous carbon box conductive agent carbon material in lithium ion battery

Through the combination of template method, high-temperature coating method and freeze-drying, a loose porous carbon box conductive agent carbon material was prepared, which solved the problems of high price and complex preparation process of existing lithium-ion battery conductive agents, and achieved excellent conductivity, low cost, good safety and environmentally friendly lithium-ion battery conductive agents, which significantly improved the battery's cycle life and stability.

CN119528134AActive Publication Date: 2025-02-28SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411312805.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-02-28
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The high price of existing lithium-ion batteries, complex preparation process and difficult dispersion, resulting in insufficient conductivity and cycle life of the battery.

Method used

The loose porous carbon box conductive carbon material was prepared by combining template method, high-temperature coating method and freeze-drying. The material is made of industrial powder salt and hot melt polymer materials by ball milling, and is coated with high temperature and graphitization to form a conductive agent with a high specific surface area and loose structure.

Benefits of technology

It realizes the lithium-ion battery conductive agent with excellent conductivity, low cost, good safety and environmentally friendly, which significantly improves the cycle life and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528134A_ABST
    Figure CN119528134A_ABST
Patent Text Reader

Abstract

The invention discloses a loose porous carbon box conductive agent carbon material as well as a preparation method and application thereof. The loose porous carbon box conductive agent carbon material is prepared by graphitizing a conductive agent carbon material precursor at a high temperature of 1200-1500 DEG C in a protective atmosphere; the conductive agent carbon material precursor is obtained by performing high-temperature coating on solid powder through a coating machine under a protective atmosphere, washing with water and freeze-drying; the solid powder is prepared by ball-milling industrial powder salt and a hot-melting high polymer material; the high-temperature coating is composed of hot melting and coke discharging, and the freeze-drying is characterized in that the washed material is dispersed in water to prepare a suspension liquid, the suspension liquid is frozen to be below the freezing point, and water in the material is directly sublimated into water vapor from solid ice in a vacuumizing mode. The loose porous carbon box conductive agent has a porous structure, and a relatively large net structure is beneficial to attachment of active substances, so that an efficient conductive network can be formed, the conductivity of electrons is enhanced, and the electrochemical performance of the lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to carbon materials, in particular to a loose porous carbon box conductive agent carbon material and a preparation method and application thereof, wherein the application is the application of the loose porous carbon box conductive agent carbon material as a negative electrode conductive agent for lithium ion batteries; the invention belongs to the technical field of negative electrode conductive agent materials for lithium ion batteries. Background Art

[0002] With the increasing shortage of non-renewable energy such as oil, there is an urgent need to seek an environmentally friendly, sustainable, green and clean new energy. As a new type of sustainable energy, lithium-ion batteries are widely used in many portable electronic products, such as mobile phones, laptops, etc., and are also used in electric vehicles and energy storage systems. The structure of lithium-ion batteries includes positive electrode, negative electrode, electrolyte and separator. During the charging process, Li + The Li migrates from the positive electrode to the negative electrode through the electrolyte, and the discharge process is the opposite. + Lithium-ion batteries can be continuously charged and discharged from the negative electrode to the positive electrode through the electrolyte. + Going back and forth between the positive and negative electrodes. Compared with other types of batteries, lithium-ion batteries have higher energy density, longer cycle life and lower self-discharge rate. However, it also has some problems, such as capacity fading, safety and cost challenges.

[0003] The normal charging and discharging process requires the participation of lithium ions and electrons. This requires that the electrodes of lithium-ion batteries must be mixed conductors of ions and electrons, and the electrode reaction can only occur at the junction of the electrolyte, conductive agent, and active material. The positive electrode active materials are mostly transition metal oxides or transition metal phosphates, which are semiconductors or insulators with poor conductivity. Although the conductivity of the negative electrode graphite material is slightly better, the expansion and contraction of the graphite material during multiple charging and discharging reduces the contact between the graphite particles, increases the gap, and even some of them are separated from the collector, becoming dead active materials and no longer participating in the electrode reaction. In lithium-ion batteries, conductive agents are one of the important components of the battery and are an indispensable key material in the high-current charging and discharging process of lithium-ion batteries. It collects microcurrents between active component substances and between active substances and current collectors, helps charge transfer between electrolytes and electrodes, and builds an efficient and robust conductive network, which can significantly increase the electron transfer rate, reduce contact resistance, and promote the penetration of electrolytes into electrodes, thereby playing an important role in improving the battery's conductivity, capacity, rate performance, and cycle performance. In addition, the conductive agent can also improve the processing of the electrode, promote the infiltration of the electrolyte into the electrode, effectively increase the migration rate of lithium ions in the electrode material, reduce polarization, and thus improve the charge and discharge efficiency and service life of the electrode. The conductive agent can fill the particle gaps generated by the expansion and contraction of the electrode material, thereby maintaining the conductivity of the electrode and improving the cycle life and stability of the battery.

[0004] According to the market price range, conductive agents can be divided into basic conductive agents and high-performance conductive agents, among which basic conductive agents include conductive carbon black, multi-arm carbon nanotubes, etc. Conductive carbon black is a conductive additive, and its structure is usually a spherical particle aggregate with a diameter of less than 100nm. Although conductive carbon black is cheap, the relatively low electronic conductivity of carbon black cannot form a good conductive network, and it has high resistance and is easy to polarize, which affects the electrochemical reaction kinetics on the cathode side and significantly reduces the efficiency of the battery. In addition, the industrial preparation of carbon black is usually achieved by burning hydrocarbon compounds. This method has poor controllability, pollutes the environment, and has poor structure and performance of the regulated products. Compared with conductive carbon black, multi-walled carbon nanotubes have excellent conductivity, but their dispersibility is poor and they are easy to agglomerate, which will affect the overall performance of the composite material; and the use of transition metal salts as catalysts in the preparation process may cause heavy metal pollution to the environment; because its wastewater contains a large amount of organic matter and acid-base substances, if improperly handled, it will cause water pollution. High-performance conductive agents include single-walled carbon nanotubes, graphene, and composites of the two. This type of conductive agent has excellent conductivity and special physical and chemical properties, but the first coulomb efficiency (ICE) of this type of conductive agent is extremely low, and the addition of this conductive agent will reduce the first coulomb efficiency of the battery. Single-walled carbon nanotubes are generally prepared by laser evaporation and chemical vapor deposition. However, the laser evaporation method has expensive equipment and high energy consumption, resulting in excessively high production costs and low output; the vapor deposition method has expensive equipment and produces toxic and corrosive by-products during the production process, which harms the environment and operators, limiting its large-scale production. At present, the preparation methods of graphene include mechanical exfoliation, chemical vapor deposition, etc., which have low output, complex technology and high cost, limiting its large-scale commercial production.

[0005] Chinese invention patent application 201710792812.8 discloses a composite conductive agent, a lithium-ion battery pole piece and a lithium-ion battery. By introducing a new composite conductive agent, a pole piece with a developed effective conductive network on the surface can be made by adding a small amount of the conductive agent, so that the prepared lithium-ion battery has excellent rate discharge, low-temperature discharge, high-temperature storage and cycle performance. The composite conductive agent in the present invention includes single-walled or few-walled carbon nanotubes and graphene nanosheets; the single-walled or few-walled carbon nanotubes have a specific surface area of ​​200-1500m 2 / g, the tube diameter is 1-10nm, and the tube length is greater than 5μm; the graphene nanosheet has a diameter of 0.2-2μm and a specific surface area of ​​less than 1800m 2 / g, and a thickness of less than 2nm. However, this technology requires the use of single-walled carbon nanotubes and graphene nanosheets, which will greatly increase the cost of the battery. In addition, the specific surface area of ​​the composite conductive agent of this technology is too high, which will lead to more side reactions during the charging and discharging process, affecting the overall first coulomb efficiency of the battery.

[0006] Based on the problems existing in the existing technology, it is imperative to develop conductive agents with low cost, environmental friendliness, scalable production, high conductivity, and high first coulombic efficiency. This is the key to improving the conductivity of lithium-ion batteries, which is very beneficial to improving the service life of lithium-ion batteries and promoting the development of lithium-ion batteries, and will promote the healthy development of the new energy industry. Summary of the invention

[0007] In order to overcome the problems of high price, complex preparation process and difficult dispersion of existing lithium-ion battery conductive agents, the present invention provides a loose porous carbon box conductive agent carbon material and a preparation method thereof which has simple process, low cost, good safety, environmental friendliness, excellent conductivity and improved battery cycle life and has the advantage of large-scale production.

[0008] Another object of the present invention is to provide an application of loose porous carbon box conductive agent carbon material in a lithium ion battery conductive agent, which can form an efficient conductive network in the lithium ion battery, provide a faster electron transmission channel and lower resistance, thereby improving the overall conductivity of the battery and improving the electrochemical performance of the battery.

[0009] The object of the present invention is achieved through the following technical solutions:

[0010] A loose porous carbon box conductive agent carbon material is prepared by high-temperature graphitization of a conductive agent carbon material precursor at 1200-1500°C under a protective atmosphere; the conductive agent carbon material precursor is obtained by high-temperature coating solid powder in a coating machine under a protective atmosphere, followed by water washing and freeze drying; the solid powder is industrial powder salt and a hot-melt polymer material obtained by ball milling, and the melting point of the industrial powder salt is higher than that of the selected hot-melt polymer material; the high-temperature coating consists of hot melting and coke removal, the hot melting temperature is 150-220°C, and the time is 1-3h; the coke removal temperature is 600-700°C, and the coke removal time is 2-4h; the freeze drying refers to dispersing the washed material in water, preparing a suspension, and then freezing it to below the freezing point, and sublimating the moisture in the material directly from solid ice to water vapor by vacuuming.

[0011] The method for preparing the loose porous carbon box conductive agent carbon material comprises the following steps:

[0012] 1) preparing uniform solid powder by ball milling industrial powdered salt and hot-melt polymer material;

[0013] 2) Under a protective atmosphere, the solid powder is coated at high temperature by a coating machine, and then washed and freeze-dried to obtain a conductive agent carbon material precursor; the high-temperature coating consists of hot melting and coking, the hot melting temperature is 150-220°C, and the time is 1-3 hours; the coking temperature is 600-700°C, and the coking time is 2-4 hours; the freeze-drying refers to dispersing the washed material in water, freezing it to below the freezing point after preparing a suspension, and sublimating the water in the material directly from solid ice to water vapor by vacuuming;

[0014] 3) Under a protective atmosphere, the conductive agent carbon material precursor is graphitized at a temperature of 1200-1500° C. to obtain a loose porous carbon box conductive agent carbon material.

[0015] To further achieve the purpose of the present invention, preferably, the ball milling time is 2.5 to 4 hours and the rotation speed is 25 to 45 rpm.

[0016] Preferably, the industrial powdered salt is one or more of sodium chloride, potassium chloride, sodium sulfate and potassium sulfate; the hot-melt polymer material is one or more of asphalt, polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF) and polyvinyl pyrrolidone (PVP).

[0017] Preferably, the mass ratio of the hot-melt polymer material to the industrial powdered salt is 0.05-0.1:1; the balls used for ball milling are zirconium balls, and the mass ratio of the zirconium balls to the material being ball milled is 0.21-0.22:1.

[0018] Preferably, the rotation speed of the coating machine is 30-45 rpm, and the flow rate of the protective atmosphere of the coating machine is 40-50 mL / min.

[0019] Preferably, the freeze-drying temperature is -60 to -40°C, and the freeze-drying time is 8 to 12 hours.

[0020] Preferably, the water washing refers to soaking the material in pure water, filtering it, and repeatedly washing it until there is no industrial powdered salt.

[0021] Preferably, the high temperature graphitization time is 3 to 4 hours, and the heating rate is 2 to 5° C. / min; in step 2) and step 3), the protective atmosphere is nitrogen or argon atmosphere.

[0022] The application of the loose porous carbon box conductive agent carbon material in preparing the negative electrode of a lithium ion battery.

[0023] Preferably, a lithium ion negative electrode material, a binder and a loose porous carbon box conductive agent carbon material are mixed to prepare a lithium ion battery negative electrode slurry, which is evenly coated on a copper foil and pressed into a sheet to obtain the lithium ion battery negative electrode plate; the lithium ion negative electrode material is a silicon carbon material (SBaS-420-L material purchased from Guangdong Dianchi Qianli New Energy Co., Ltd., which is a silicon / amorphous carbon / graphite composite material with a reversible capacity of approximately 420 mAh / g), the binder is TRD-104A (TRD binder specifically for lithium ion batteries) and CMC (sodium carboxymethyl cellulose), and the mass ratio of the negative electrode material, the binder and the loose porous carbon box conductive agent carbon material is: (95-96): (2-4): (1-2).

[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0025] 1) Existing technologies for preparing conductive agents for lithium-ion batteries include burning hydrocarbon compounds and chemical vapor deposition. The method of preparing conductive agent materials by burning hydrocarbon compounds has poor controllability, pollutes the environment, and has poor control over the structure and performance of the product. The chemical vapor deposition method consumes a large amount of energy to maintain a high temperature environment, which not only increases the preparation cost, but also imposes a certain burden on the environment. In addition, the low output makes it difficult to achieve large-scale, continuous and stable production. In order to solve the problems in the use of conductive agent materials and further improve the performance of lithium-ion batteries, the present invention prepares loose porous carbon box conductive agent carbon materials by combining a template method, a high-temperature coating method and freeze drying. The high-temperature coating process has the advantages of simple method, strong operability, low cost, and the ability to quickly and massively wrap the organic carbon source directly on the surface of the sacrificial agent.

[0026] 2) The present invention uses industrial powder salt as a hard template because industrial powder salt has a higher melting point than the selected hot-melt polymer, is easily soluble in water, and has low cost. The carbon material after removing the template is in the shape of a carbon box. The conductive agent designed in this way has a higher specific surface area and presents many loose void structures on the surface, which can more easily provide more reactive surfaces and fill the particle gaps generated by the expansion and contraction of the electrode material, thereby maintaining the conductivity of the electrode and improving the cycle life and stability of the battery. The larger two-dimensional network structure is also conducive to increasing the adsorption of substances, providing a conductive bridge between active substances, allowing lithium ions to enter and diffuse more easily, thereby improving the overall conductivity of the battery.

[0027] 3) The loose porous carbon box conductive agent carbon material of the present invention is prepared at high temperature and has good high temperature resistance, which enables the lithium ion battery to operate stably for a long time under high temperature conditions; it can form a continuous conductive network in the electrode, enhance the conduction ability of electrons, and improve the performance of lithium ion batteries, especially the high temperature performance of lithium ion batteries will be significantly improved. The test results of the embodiment show that the loose porous carbon box conductive agent carbon material has a large surface area, which can significantly reduce the internal resistance of lithium ion batteries and greatly improve the cycle stability of lithium ion batteries.

[0028] 4) The loose porous carbon mesh conductive agent obtained by the present invention has a porous structure, and the larger mesh structure is conducive to the attachment of active substances, can form an efficient conductive network, enhance the conduction ability of electrons, provide faster electron transmission channels and lower resistance, improve the overall conductivity of the battery, and thus improve the electrochemical performance of lithium-ion batteries.

[0029] 5) The loose porous carbon box conductive agent carbon material synthesized by the present invention can be used as a negative electrode conductive agent for lithium ion batteries. For example, when the mass ratio of industrial powdered salt and asphalt is 40:3, the electrochemical test results of the silicon carbon material as a conductive agent show that the material performs better than SP: at 25°C and a current density of 0.1C, it has a first coulomb efficiency of >90%; after 800 cycles at a rate of 1C, the capacity retention rate of the material is 90.46%; after 1000 cycles at a rate of 0.75C, the capacity retention rate of the material is 87.87%.

[0030] 6) The raw materials used in the present invention have a wide range of sources and a variety of preparation methods, which provides a reference idea for people to prepare lithium-ion battery conductive agent materials with excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The XRD diagrams of the conductive agent carbon material precursor before graphitization and the porous carbon box conductive agent carbon material after graphitization prepared in Example 1 are shown.

[0032] Figure 2 This is the nitrogen adsorption-desorption curve of the carbon box conductive agent carbon material prepared in Example 1.

[0033] Figure 3 This is the pore size distribution diagram of the carbon box conductive agent carbon material prepared in Example 1.

[0034] Figure 4 This is the SEM image of the carbon box conductive agent carbon material prepared in Example 1.

[0035] Figure 5 The first three charge and discharge curves of the lithium ion half-cell prepared in Example 1 at 25° C. and 0.1C rate are shown.

[0036] Figure 6 This is a graph showing the long cycle performance test results of the lithium ion half-cells prepared in Example 1 and Comparative Example 1 at a 1C rate.

[0037] Figure 7 This is a long cycle performance diagram of the lithium ion half-cell prepared in Example 1 after 1000 cycles at a 0.75C rate.

[0038] Figure 8 This is a comparison chart of the lithium ion diffusion rates of the lithium ion half-cells prepared in Example 1 and Comparative Example 1 during the charging process.

[0039] Fig. 9 The figure is a comparison chart of the lithium ion diffusion rates of the lithium ion half-cells prepared in Example 1 and Comparative Example 1 during the discharge process. Specific implementation methods

[0041] The present invention is further described below in conjunction with examples, comparative examples and accompanying drawings, but the embodiments of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.

[0042] The present invention is characterized in that loose porous carbon box conductive agent carbon material is prepared by the coordinated cooperation of template method, high temperature coating method and freeze drying. The template method uses industrial powder salt as a hard template, and industrial powder salt and hot-melt polymer material are ball-milled to obtain solid powder material. The industrial powder salt has the characteristics of higher melting point than the selected hot-melt polymer, easy to dissolve in water and low cost. The carbon material after removing the template is in the shape of a carbon box. The conductive agent designed in this way has a higher specific surface area and the surface presents many loose void structures, which is easier to provide more reactive surfaces, can fill the particle gaps generated by the expansion and contraction of the electrode material, thereby maintaining the conductive performance of the electrode and improving the cycle life and stability of the battery. The larger two-dimensional mesh structure is also conducive to increasing the adsorption of substances, providing a conductive bridge between active substances, allowing lithium ions to enter and diffuse more easily, thereby improving the overall conductivity of the battery.

[0043] High-temperature coating consists of hot melting and coking, and is characterized by controlling the hot melting temperature to 150-220°C for 1-3 hours; the coking temperature to 600-700°C, and the coking time to 2-4 hours; under a protective atmosphere, the solid powder material is subjected to high-temperature coating by a coating machine, and then washed and freeze-dried to obtain a conductive agent carbon material precursor. Freeze-drying means that the washed material is dispersed in water, prepared into a suspension, and then frozen to below the freezing point, and the water in the material is directly sublimated from solid ice to water vapor by vacuuming. The high-temperature coating process of the present invention has the advantages of simple method, strong operability, low cost, and the ability to quickly and massively coat the organic carbon source directly on the surface of the sacrificial agent. The obtained conductive agent carbon material precursor is subjected to high-temperature graphitization at 1200-1500° C. under a protective atmosphere to obtain a loose porous carbon box conductive agent carbon material, wherein the loose porous carbon box conductive agent carbon material presents a two-dimensional self-assembled mesh carbon box structure with a large number of pores distributed inside; the conductive carbon material has macropores, micropores and / or mesopores, the size of the cubic pores of the self-assembled mesh carbon box is 4-15 μm, the size of the surface pores is 20-100 nm, and the specific surface area is 100-240 m 2 / g; the tap density of loose carbon box conductive agent is 1.0~1.8g / cm 3 .

[0044] As can be seen from the above, a loose porous carbon box conductive agent carbon material of the present invention is obtained by high-temperature graphitization of a conductive agent carbon material precursor at 1200-1500°C under a protective atmosphere; the conductive agent carbon material precursor is obtained by high-temperature coating a solid powder through a coating machine under a protective atmosphere, followed by water washing and freeze-drying; the solid powder is obtained by ball milling industrial powder salt and a hot-melt polymer material, and the melting point of the industrial powder salt is higher than that of the selected hot-melt polymer material; the high-temperature coating consists of hot melting and coking, and the hot melting temperature is 150-220°C and the time is 1-3h; the coking temperature is 600-700°C and the coking time is 2-4h; the freeze-drying refers to dispersing the washed material in water, preparing a suspension and freezing it below the freezing point, and sublimating the moisture in the material directly from solid ice to water vapor by vacuuming.

[0045] The method for preparing the above-mentioned loose porous carbon box conductive agent carbon material comprises the following steps:

[0046] 1) preparing uniform solid powder by ball milling industrial powdered salt and hot-melt polymer material;

[0047] 2) Under a protective atmosphere, the solid powder is coated at high temperature by a coating machine, and then washed and freeze-dried to obtain a conductive agent carbon material precursor; the high-temperature coating consists of hot melting and coking, the hot melting temperature is 150-220°C, and the time is 1-3 hours; the coking temperature is 600-700°C, and the coking time is 2-4 hours; the freeze-drying refers to dispersing the washed material in water, freezing it to below the freezing point after preparing a suspension, and sublimating the water in the material directly from solid ice to water vapor by vacuuming;

[0048] 3) Under a protective atmosphere, the conductive agent carbon material precursor is graphitized at a temperature of 1200-1500° C. to obtain a loose porous carbon box conductive agent carbon material.

[0049] As for the ball milling process control involved in the above preparation method; the selection of industrial powdered salt and hot-melt polymer materials, the usage ratio range of hot-melt polymer materials and industrial powdered salt, the specific control process of the coating machine, the temperature and time control of freeze-drying, the specific method of water washing, and the time and heating rate of high-temperature graphitization can all be obtained through optimization according to the requirements of the above-mentioned template method, the requirements of high-temperature coating and the purpose of the present invention, combined with the common sense in the field.

[0050] The obtained loose porous carbon box conductive agent carbon material can be used in the preparation of lithium ion battery negative electrode. Specifically, the lithium ion negative electrode material, the binder and the loose porous carbon box conductive agent carbon material are mixed to prepare the lithium ion battery negative electrode slurry, which is evenly coated on the copper foil and pressed to obtain the lithium ion battery negative electrode sheet; the lithium ion negative electrode material is silicon carbon material, the binder is TRD-104A and CMC, and the mass ratio of the negative electrode material, the binder and the loose porous carbon box conductive agent carbon material is: (95-96): (2-4): (1-2).

[0051] The feasibility of the above loose porous carbon box conductive agent carbon material and its preparation method is verified through specific embodiments and comparative examples below, and the performance advantages of the loose porous carbon box conductive agent carbon material prepared by the above template method, high temperature coating method and freeze-drying in synergistic combination in terms of cycle stability compared with similar materials in the prior art are demonstrated through tests and comparative examples. In particular, the three-step approach of the embodiment embodies the process advantages of the present invention in terms of low cost, safety and environmental friendliness.

[0052] Example 1

[0053] A method for preparing a loose porous carbon box conductive agent carbon material comprises the following steps:

[0054] (1) Weigh 2 kg of industrial NaCl powder, 150 g of asphalt, and 10 kg of zirconium oxide balls into a ball mill and mill them at 30 rpm for 3 h using a high-energy ball mill. After milling, separate the zirconium balls using a vibrating sieve to obtain a uniform brown powder.

[0055] (2) The powder obtained in the previous step was subjected to high-temperature coating in a high-temperature coating machine. The speed of the coating machine was 40 rpm, the flow rate of the inert gas (argon) was 40 mL / min, and the temperature was raised to 200°C at a rate of 200°C / h, and kept at that temperature for 1 hour; then raised to 600°C at a rate of 200°C / h, and kept at that temperature for 2 hours. After coating, a black powder with a small amount of blocky solid was obtained.

[0056] (3) The solid blocks in the coated material are removed by a vibrating screen, and the NaCl is removed by washing and filtering. The washed material is then dispersed in 2L of pure water and freeze-dried using a freeze dryer: the freeze-drying temperature is -50°C, the time is 9h, and the freeze-drying obtains a fluffy conductive carbon material precursor. The obtained conductive carbon material precursor is graphitized in a tubular furnace: the temperature is raised to 1300°C at 5°C / min under an argon atmosphere, and the temperature is kept for 4h to obtain the final loose porous carbon box conductive carbon material.

[0057] This embodiment provides a lithium ion half-cell: 1.425g of silicon-carbon composite material (SBaS-420-L material purchased from Guangdong Dianchi Qianli New Energy Co., Ltd., which is a silicon / amorphous carbon / graphite composite material with a reversible capacity of approximately 420mAh / g), 0.027g of CMC (sodium carboxymethyl cellulose), 0.033g of TRD (TRD binder specifically for lithium ion batteries) and 0.015g of the prepared loose porous carbon box conductive agent carbon material are mixed, fully ground in a mortar and moved to a finger bottle, 15ml of distilled water is added, and after magnetic stirring for 12h, the material is coated on a flat copper foil with a glass rod. After the material is dried, it is pressed into a sheet to form an electrode, a metal lithium sheet is used as a counter electrode, and a CR2016 button battery is assembled in a glove box.

[0058] Figure 1The XRD diagrams of the conductive agent carbon material precursor before graphitization and the porous carbon box conductive agent carbon material after graphitization obtained in Example 1. It can be seen that the XRD spectrum has two diffraction peaks, located at about 25° and 43°, respectively, corresponding to the two crystal planes (002) and (100). Generally speaking, the (002) crystal plane of the material represents the longitudinal size of its graphite micro-chip layer. The higher and narrower the shape of the characteristic diffraction peak is, the more regular the arrangement of the micro-chip layer in space is, and the greater the degree of mutual orientation is. And the position of the (002) diffraction peak is related to the interlayer spacing of the graphite microcrystals. The more the peak position is biased to the right, the smaller the interlayer spacing is, and the more tightly the graphite microcrystals are arranged. The (100) crystal plane represents the lateral size of the microcrystal. The higher and narrower the shape of the characteristic diffraction peak is, the larger the diameter of the graphite micro-chip layer is, and the higher the degree of ring condensation is. It can be clearly seen that, compared with the sample before graphitization, the (002) peak of GHC shifted to the right and the peak shape became narrower, which indicates that the interlayer spacing of the conductive carbon box decreased and the crystallinity increased after the reaction.

[0059] Figure 2 This is the nitrogen adsorption-desorption curve of the carbon box conductive agent carbon material obtained in Example 1. It can be seen from the figure that the specific surface area of ​​the material is 238.09 m 2 g -1 A larger specific surface area can provide more active surfaces, thereby improving the catalytic effect and reaction rate of the battery. It can also improve the carrying capacity of the electrode material, promote electron transport and ion diffusion, and reduce the resistance of the electrochemical reaction.

[0060] Figure 3 This is a pore size distribution diagram of the carbon material of the carbon box conductive agent prepared in Example 1. The mesopore and micropore structure on the surface of the material is conducive to accelerating the penetration of the electrolyte and shortening the transmission path of lithium ions.

[0061] Figure 4 This is a SEM image of the carbon box conductive agent carbon material obtained in Example 1. The carbon box conductive agent carbon material presents a two-dimensional self-assembled mesh carbon box structure, with a large number of loose small holes distributed inside; the size of the cubic holes of the self-assembled mesh carbon box is 4 to 15 μm, and the size of the surface pores is 20 to 100 nm. The larger sheet structure indicates that the contact between the conductive agent and the active material is point-to-surface contact rather than the conventional point-to-point contact form, which can maximize the role of the conductive agent and reduce the amount of the conductive agent. When the amount added is small, a conductive network can be better formed. In addition, the material has many small pore structures, which is conducive to providing abundant lithium ion diffusion migration paths and electron transmission paths, accelerating the penetration process of the electrolyte.

[0062] Figure 5The first three charge-discharge curves of the lithium-ion half-cell prepared in Example 1 at 25°C and 0.1C rate are shown in the figure. As can be seen from the figure, the first coulomb efficiency of the composite material prepared with the carbon box as the conductive agent is about 91%, and the constant current charge-discharge curves of the first three cycles are basically overlapped, indicating that the material has good cycle stability.

[0063] Figure 6 The figure is a graph showing the long cycle performance test results at 1C rate for the lithium ion half-cells prepared in Example 1 and Comparative Example 1. It can be seen from the figure that after 800 cycles, the capacity retention rate of the material is 90.46%, indicating that the material has excellent electrochemical stability.

[0064] Figure 7 This is a long cycle performance diagram of the lithium ion half-cell prepared in Example 1 after 1000 cycles at a rate of 0.75C. It can be seen from the figure that after 1000 cycles, the capacity retention rate of the material is 87.87%, indicating that the material has excellent electrochemical stability.

[0065] Figure 8 and Fig. 9 The figures are respectively a comparison of the lithium ion diffusion rates of the lithium ion half-cells prepared in Example 1 and Comparative Example 1 during the charge and discharge process, wherein Figure 8 Represents the discharge process, Fig. 9 It indicates the charging process. From the figure, it can be calculated that the average lithium ion diffusion rate of the lithium ion half-cell during the charging and discharging process is: 8.205*10 -10 cm 2 ·s -1 (discharge) and 8.459*10 -10 cm 2 ·s -1 (Charging), compared with Comparative Example 1 (7.09*10 -10 cm 2 ·s -1 ) and Comparative Example 2 (7.15*10 -10 cm 2 ·s -1 ) Compared with the average lithium ion diffusion rate during half-cell charging, the lithium ion transport capacity is improved to a certain extent.

[0066] Example 2

[0067] A method for preparing a loose porous carbon box conductive agent carbon material comprises the following steps:

[0068] (1) Weigh 2 kg of industrial NaCl powder, 100 g of asphalt, and 10 kg of zirconium oxide balls into a ball mill and mill them at 25 rpm for 4 h using a high-energy ball mill. After milling, separate the zirconium balls using a vibrating sieve to obtain a uniform brown powder.

[0069] (2) The powder obtained above was subjected to high-temperature coating in a high-temperature coating agent, the coating machine speed was 30 rpm, the inert gas (argon) flow rate was 40 mL / min, and the temperature program was: heating to 150°C at a heating rate of 200°C / h, and keeping the temperature for 1.5 hours; then heating to 600°C at a heating rate of 200°C / h, and keeping the temperature for 4 hours. After coating, black powder with a small amount of blocky solid was obtained.

[0070] (3) The solid blocks in the coated material are removed by a vibrating screen, and the NaCl is removed by washing and filtering. The washed material is then dispersed in 2L of pure water and freeze-dried using a freeze dryer: the freeze-drying temperature is -40°C, the time is 10 hours, and the freeze-drying obtains a fluffy conductive carbon material precursor. The obtained conductive carbon material precursor is graphitized in a tubular furnace: the temperature is raised to 1200°C at 3°C / min under an argon atmosphere, and the temperature is kept for 4 hours to obtain the final loose porous carbon box conductive carbon material.

[0071] This embodiment provides a lithium ion half-cell: the CR2016 button cell process is the same as that of embodiment 1.

[0072] Example 3

[0073] A method for preparing a loose porous carbon box conductive agent carbon material comprises the following steps:

[0074] (1) Weigh 2 kg of industrial NaCl powder, 200 g of asphalt, and 10 kg of zirconium oxide balls into a ball mill and mill them at 40 rpm for 2.5 h using a high-energy ball mill. After milling, separate the zirconium balls using a vibrating sieve to obtain a uniform brown powder.

[0075] (2) The powder obtained above was subjected to high-temperature coating in a high-temperature coating agent. The speed of the coating machine was 45 rpm, the flow rate of the inert gas (argon) was 40 mL / min, and the temperature was raised to 250°C at a rate of 200°C / h, and kept at that temperature for 2 h; then raised to 700°C at a rate of 200°C / h, and kept at that temperature for 3 h. After coating, a black powder with a small amount of blocky solid was obtained.

[0076] (3) The solid blocks in the coated material are removed by a vibrating screen, and the NaCl is removed by washing and filtering. The washed material is then dispersed in 2L of pure water and freeze-dried using a freeze dryer: the freeze-drying temperature is -30°C, the time is 12h, and the freeze-drying obtains a fluffy conductive carbon material precursor. The obtained conductive carbon material precursor is graphitized in a tubular furnace: the temperature is raised to 1500°C at 2°C / min under an argon atmosphere, and the temperature is kept for 3h to obtain the final loose porous carbon box conductive carbon material.

[0077] This embodiment provides a lithium ion half-cell: the CR2016 button cell process is the same as that of embodiment 1.

[0078] Example 4

[0079] A method for preparing a loose porous carbon box conductive agent carbon material comprises the following steps:

[0080] (1) Weigh 2 kg of industrial NaCl powder, 100 g of polyvinyl chloride, and 10 kg of zirconium oxide balls into a ball mill and mill them at 45 rpm for 4 h using a high-energy ball mill. After milling, separate the zirconium balls using a vibrating sieve to obtain a uniform powder.

[0081] (2) The powder obtained above was subjected to high-temperature coating in a high-temperature coating agent, the coating machine speed was 40 rpm, the inert gas (argon) flow rate was 40 mL / min, and the temperature program was: heating to 180°C at a heating rate of 200°C / h, and keeping the temperature for 2 hours; then heating to 700°C at a heating rate of 200°C / h, and keeping the temperature for 2 hours. After coating, black powder with a small amount of blocky solid was obtained.

[0082] (3) The solid blocks in the coated material are removed by a vibrating screen, and the NaCl is removed by washing and filtering. The washed material is then dispersed in 2L of pure water and freeze-dried using a freeze dryer: the freeze-drying temperature is -50°C, the time is 8h, and the freeze-drying obtains a fluffy conductive carbon material precursor. The obtained conductive carbon material precursor is graphitized in a tubular furnace: the temperature is raised to 1200°C at 5°C / min under an argon atmosphere, and the temperature is kept for 4h to obtain the final loose porous carbon box conductive carbon material.

[0083] This embodiment provides a lithium ion half-cell: the CR2016 button cell process is the same as that of embodiment 1.

[0084] Example 5

[0085] A method for preparing a loose porous carbon box conductive agent carbon material comprises the following steps:

[0086] (1) Weigh 2 kg of industrial NaCl powder, 150 g of polyvinylidene fluoride, and 10 kg of zirconium oxide balls into a ball mill and mill them at 30 rpm for 4 h using a high-energy ball mill. After milling, separate the zirconium balls using a vibrating sieve to obtain a uniform powder.

[0087] (2) The powder obtained above was subjected to high-temperature coating in a high-temperature coating agent, the coating machine speed was 40 rpm, the inert gas (argon) flow rate was 40 mL / min, and the temperature program was: heating to 220°C at a heating rate of 200°C / h, and keeping the temperature for 3 hours; then heating to 600°C at a heating rate of 200°C / h, and keeping the temperature for 3 hours. After coating, black powder with a small amount of blocky solid was obtained.

[0088] (3) The solid blocks in the coated material are removed by a vibrating screen, and the NaCl is removed by washing and filtering. The washed material is then dispersed in 2L of pure water and freeze-dried using a freeze dryer: the freeze-drying temperature is -50°C, the time is 10h, and the freeze-drying obtains a fluffy conductive carbon material precursor. The obtained conductive carbon material precursor is graphitized in a tubular furnace: the temperature is raised to 1300°C at 5°C / min under an argon atmosphere, and the temperature is kept for 3h to obtain the final loose porous carbon box conductive carbon material.

[0089] A lithium ion half-cell: CR2016 button cell. The process is the same as that in Example 1.

[0090] Example 6

[0091] This example provides a method for preparing a loose porous carbon box conductive agent carbon material, comprising the following steps:

[0092] (1) Weigh 2 kg of industrial NaCl powder, 100 g of polyvinyl pyrrolidone, and 10 kg of zirconium oxide balls into a ball mill and mill them at 40 rpm for 4 h using a high-energy ball mill. After milling, separate the zirconium balls using a vibrating sieve to obtain a uniform powder.

[0093] (2) The powder obtained above was subjected to high-temperature coating in a high-temperature coating agent, the coating machine speed was 45 rpm, the inert gas (argon) flow rate was 40 mL / min, and the temperature program was: heating to 180°C at a heating rate of 200°C / h, and keeping the temperature for 1 hour; then heating to 700°C at a heating rate of 200°C / h, and keeping the temperature for 2 hours. After coating, black powder with a small amount of blocky solid was obtained.

[0094] (3) The solid blocks in the coated material are removed by a vibrating screen, and the NaCl is removed by washing and filtering. The washed material is then dispersed in 2L of pure water and freeze-dried using a freeze dryer: the freeze-drying temperature is -50°C, the time is 9h, and the freeze-drying obtains a fluffy conductive carbon material precursor. The obtained conductive carbon material precursor is graphitized in a tubular furnace: the temperature is raised to 1300°C at 5°C / min under an argon atmosphere, and the temperature is kept for 4h to obtain the final loose porous carbon box conductive carbon material.

[0095] This embodiment provides a lithium ion half-cell: the CR2016 button cell process is the same as that of embodiment 1.

[0096] Comparative Example 1

[0097] A lithium ion half-cell: CR2016 button cell. The process is the same as that of Example 1, except that the conductive agent material is changed. The conductive agent used is conductive carbon black SP.

[0098] Comparative Example 2

[0099] A lithium ion half-cell: CR2016 button cell. The process is the same as that of Example 1, except that the conductive agent material is changed, and the conductive agent used is multi-walled carbon tubes.

[0100] Performance Testing

[0101] The conductive agent materials prepared by the above-mentioned embodiments and comparative example steps are characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), specific surface area measurement (BET) and four-probe resistance tester (Four-probe Tester) to analyze the material morphology, component content, type of chemical bonds and other information.

[0102] The conductive agent materials prepared by the above-mentioned embodiments and comparative examples are tested for long-cycle stability, high-current interference resistance and lithium storage performance of the surfaces of the materials obtained in the embodiments and comparative examples by constant current charge and discharge and long-cycle testing.

[0103] The present invention mainly utilizes conductive carbon materials with good conductivity, simple preparation process and environmental friendliness, and prepares loose porous carbon box conductive carbon materials by combining template method, high temperature coating method and freeze drying as negative electrode conductive agents for lithium ion batteries. After the batteries prepared in the above embodiments were set aside for 24 hours, a battery tester (Shenzhen Xinwei) and BTS8.0.0 software were used. The test temperature was 25°C and the current density was 0.1-3C. Constant current charge and discharge (discharge cut-off voltage 0.005V, charge cut-off voltage 2V) were performed on various types of batteries to test the long-term cycle performance of the battery. The preparation characteristics and electrochemical properties of the samples of Examples 1 to 6 are detailed in Table 1, and the electrochemical properties of the lithium ion half-cell prepared in Comparative Example 1 are detailed in Table 2.

[0104] Table 1 Characteristics of the conductive agents prepared in Examples 1 to 6 and electrochemical test results of lithium ion half-cells at 25°C

[0105]

[0106] Table 2 Characteristics of the conductive agent of Comparative Example 1 and electrochemical test results of lithium ion half-cell at 25°C

[0107]

[0108] According to the test results in Table 1 and Table 2, the prepared conductive carbon box conductive agent has a lower resistivity than the conductive carbon black SP and multi-walled carbon tubes in the prior art, indicating better conductivity. And the specific surface area is much higher than SP, which can provide more active surface, thereby improving the catalytic effect and reaction rate of the battery, and at the same time can also improve the carrying capacity of the electrode material, promote electron transport and ion diffusion, and reduce the resistance of the electrochemical reaction. The electrochemical performance measured by using the material prepared by the present invention as a negative electrode conductive agent for lithium ion batteries is significantly better than that of traditional conductive carbon black and multi-walled carbon tubes.

[0109] It can be clearly seen from the test results in Table 1 and Table 2 that the cycle performance of the lithium-ion half-cell prepared using the carbon box in the embodiment is significantly better than that of the comparative example. This is because the prepared conductive carbon box has a two-dimensional, ultra-thin structural feature, and the mesh carbon box structure indicates that the conductive agent and the active material are in "surface-point" contact. Compared with the "point-line" contact between the carbon tube and the active material, and the "point-point" contact between the carbon black and the active material, a good conductive network can be constructed by overlapping the mesh conductive agent at a smaller usage amount, greatly improving the conductivity of the entire electrode. Therefore, the conductivity threshold of the entire electrode can be reached at a smaller usage amount, so that the active material exhibits better electrochemical properties and improves the energy density of the battery. Since the conductive carbon box can better form a conductive network, the conductive effect is much better than that of conductive carbon black and multi-walled carbon tubes.

[0110] From the comparison of Examples 1 to 3, it can be seen that based on the same asphalt carbon source, the mass ratio of powder salt to carbon source of 2Kg:150g shows better cycle stability and conductivity. This is because if the carbon layer is too thick, it will hinder the diffusion of lithium ions and reduce the ionic conductivity of the electrode, and if the carbon layer is too thin, the conductive material is easy to break.

[0111] It can be seen from the comparison of Examples 1 to 6 that when the carbon source is asphalt and the mass ratio of the carbon source to industrial powdered salt is 3:40, the specific surface area of ​​the conductive agent is 238.09 m 2 ·g -1 , the resistivity is 0.035Ω·cm. The performance of the silicon-carbon material is tested using the present invention as a conductive agent. After 800 cycles at a rate of 1C, the capacity retention rate of the material is as high as 90.46%. The capacity retention rates of other embodiments of the present invention are also at the same order of magnitude.

[0112] It can be seen from the above embodiments and comparative examples that the present invention has the following characteristics:

[0113] The present invention uses a high temperature process as the main preparation process, quickly and effectively coats the carbon source on the surface of industrial powder salt, and then graphitizes it at a high temperature. At the same time, industrial powder salt is combined as a sacrificial agent and a pore-forming agent to participate in the precursor synthesis. At the same time, the raw materials required for the process are widely available and low in cost; the raw materials and chemical reagents involved in the process are all common medicines, which are environmentally friendly and low in cost; in summary, the present invention has the potential for large-scale commercial production.

[0114] The loose porous carbon box conductive agent carbon material of the present invention presents a two-dimensional self-assembled mesh carbon box structure, and a large number of loose pore structures are distributed inside it. This structure enables the conductive agent to form a continuous conductive network in the electrode active material, thereby enhancing the conduction ability of electrons.

[0115] The loose porous carbon box conductive agent carbon material of the present invention has excellent conductivity and has great application potential in the field of lithium ion batteries.

[0116] The loose porous carbon box conductive agent carbon material of the present invention can be made into a pole piece with a developed effective conductive network on the surface when a small amount of the conductive agent is added, so that the prepared lithium ion battery has excellent cycle performance. The present invention is not only low-cost and can be mass-produced, but also has a suitable specific surface area, which solves the problems of high cost, non-scale production and excessive specific surface area affecting the initial coulomb efficiency of the conductive agent used in Chinese invention patent application 201710792812.8.

[0117] In general, the present invention mainly uses different hot-melt polymer materials to coat the surface of industrial powder salt under high temperature conditions, then washes away the powder salt after carbonization, freeze-dries it and graphitizes it at high temperature to finally obtain a loose porous carbon box conductive agent carbon material. The sheet structure of the conductive agent can better form a conductive network, improve the overall conductivity of the battery, and improve the cycle stability of the material. In addition, the material has many small pore structures, which is conducive to providing abundant lithium ion diffusion migration paths and electron transmission paths, accelerating the penetration process of the electrolyte.

[0118] The above embodiments are partial implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.

Claims

1. A loose porous carbon box conductive agent carbon material, characterized in that: It is prepared by high-temperature graphitization of a conductive agent carbon material precursor at 1200-1500°C under a protective atmosphere; the conductive agent carbon material precursor is obtained by high-temperature coating solid powder in a coating machine under a protective atmosphere, followed by water washing and freeze-drying; the solid powder is industrial powder salt and a hot-melt polymer material obtained by ball milling, and the melting point of the industrial powder salt is higher than that of the selected hot-melt polymer material; the high-temperature coating consists of hot melting and coke removal, the hot melting temperature is 150-220°C, and the time is 1-3h; the coke removal temperature is 600-700°C, and the coke removal time is 2-4h; the freeze-drying refers to dispersing the washed material in water, preparing a suspension, and then freezing it to below the freezing point, and sublimating the moisture in the material directly from solid ice to water vapor by vacuuming.

2. The method for preparing the loose porous carbon and conductive agent carbon material according to claim 1, characterized in that The steps include: 1) preparing uniform solid powder by ball milling industrial powdered salt and hot-melt polymer material; 2) Under a protective atmosphere, the solid powder is coated at high temperature by a coating machine, and then washed and freeze-dried to obtain a conductive agent carbon material precursor; the high-temperature coating consists of hot melting and coking, the hot melting temperature is 150-220°C, and the time is 1-3 hours; the coking temperature is 600-700°C, and the coking time is 2-4 hours; the freeze-drying refers to dispersing the washed material in water, freezing it to below the freezing point after preparing a suspension, and sublimating the water in the material directly from solid ice to water vapor by vacuuming; 3) Under a protective atmosphere, the conductive agent carbon material precursor is graphitized at a temperature of 1200-1500° C. to obtain a loose porous carbon box conductive agent carbon material.

3. The method for preparing the loose porous carbon and conductive agent carbon material according to claim 2, characterized in that: The ball milling time is 2.5 to 4 hours, and the rotation speed is 25 to 45 rpm.

4. The method for preparing the loose porous carbon and conductive agent carbon material according to claim 2, characterized in that: The industrial powdered salt is one or more of sodium chloride, potassium chloride, sodium sulfate and potassium sulfate; the hot-melt polymer material is one or more of asphalt, polyvinyl chloride, polyvinylidene fluoride and polyvinyl pyrrolidone.

5. The method for preparing the loose porous carbon and conductive agent carbon material according to claim 2, characterized in that: The mass ratio of the hot-melt polymer material to the industrial powdered salt is 0.05-0.1:1; the balls used for ball milling are zirconium balls, and the mass ratio of the zirconium balls to the material to be ball milled is 0.21-0.22:

1.

6. The method for preparing the loose porous carbon and conductive agent carbon material according to claim 2, characterized in that: The rotation speed of the coating machine is 30-45 rpm, and the flow rate of the protective atmosphere of the coating machine is 40-50 mL / min.

7. The method for preparing the loose porous carbon and conductive agent carbon material according to claim 2, characterized in that: The freeze-drying temperature is -60 to -40°C, and the freeze-drying time is 8 to 12 hours.

8. The method for preparing the loose porous carbon and conductive agent carbon material according to claim 2, characterized in that: The water washing refers to soaking the material in pure water, filtering it, and repeatedly washing it until there is no industrial powdered salt.

9. The method for preparing the loose porous carbon and conductive agent carbon material according to claim 2, characterized in that: The high temperature graphitization time is 3 to 4 hours, and the heating rate is 2 to 5°C / min; in step 2) and step 3), the protective atmosphere is nitrogen or argon atmosphere.

10. Use of the loose porous carbon box conductive agent carbon material according to claim 1 in preparing a negative electrode of a lithium ion battery.

11. The use of the loose porous carbon box conductive agent carbon material in preparing a negative electrode of a lithium ion battery according to claim 10, characterized in that: A lithium ion negative electrode material, a binder and a loose porous carbon box conductive agent carbon material are mixed to prepare a lithium ion battery negative electrode slurry, which is evenly coated on a copper foil and pressed into a sheet to obtain the lithium ion battery negative electrode sheet; the lithium ion negative electrode material is a silicon carbon material, the binder is TRD-104A and CMC, and the mass ratio of the negative electrode material, the binder and the loose porous carbon box conductive agent carbon material is: (95-96): (2-4): (1-2).

Citation Information

Patent Citations

  • Composite conductive agent, lithium ion battery pole pieces and lithium ion battery

    CN107482222A

  • Composite carbon material conductive agent

    CN107579250A

  • Modulation method of morphology and structure transformation of nano carbon material based on crystallization induction

    CN110790257A

  • Method of preparing a porous carbon material

    US20170240424A1

  • Conductive agent, electrode for lithium battery, and method for preparing conductive agent

    WO2024109728A1

Cited By

  • Self-assembled elastic conductive silicon carbon microsphere, preparation method thereof and application of self-assembled elastic conductive silicon carbon microsphere in lithium ion battery

    CN122426728A